INFLUENCE OF AUDIT COMMITTEE COMPETENCE, AUDIT COMMITTEE INDEPENDENCE, INDEPENDENT COMMISSIONER AND LEVERAGE ON TAX AGGRESSIVENESS - Ni Putu Ayu Arismajayanti; I Ketut Jati (Master of Accounting Universitas Trunojoyo Madura, 2017)
Tax is an important element in sustaining the government budget and an obligation that must be fulfilled by taxpayers, both individual and legal entity. The unfulfilled tax revenue target in Indonesia is caused by several factors. One of them is that there is an indication that company as the taxpayer of a legal entity commits tax aggressiveness. There is a difference of interest between the company and the government that causes the company to arrange a plan for reducing the cost of corporate taxes both legally and illegally. This study aims to obtain empirical evidence of the influence of audit committee competence, audit committee independence, independent commissioner and leverage on tax aggressiveness. The object in this study was manufacturing companies listed on the Indonesia Stock Exchange period 2013-2016. The sample used in this study was 176 companies selected by purposive sample by using multiple linear regression analysis technique. The results of this study indicate that the audit committee competence and independent commissioner variables have no effect on tax aggressiveness, audit committee independence has a negative effect on tax aggressiveness, and leverage has a positive effect on tax aggressiveness.